Histomorphological Studies on Distribution of Hair Follicles in Different Breeds of Rabbits - Lucy, K.M. (Indian Journal of Veterinary Anatomy, 2019)
Histomorphological studies on the distribution of hair follicles were conducted on the skin of six breeds of rabbits. All the rabbits showed primary and secondary follicles with sebaceous glands. Arrangement of hair follicles showed some differences among the breeds. In Angora, the compound hair follicle consisted of one primary hair follicle and six to twelve secondary follicles; in White Giant, there were six to eight secondary follicles per primary follicle. In New Zealand White, each compound hair follicle was formed of a primary hair follicle in the centre. Surrounding this, three to four small clusters of secondary follicles were found with six to twelve secondary follicles in each cluster. In Soviet Chinchilla, Grey Giant and crossbred, two to three clusters of secondary follicles surrounded the primary follicle, and the number of secondary follicles per cluster was also less (three to seven).